Fundamentals of corporate finance - Berk, Jonathan, 1962-; Harford, Jarrad; Demarzo, Peter (Boston [etc.] Pearson Education, 2015)
For MBA/graduate students taking a course in corporate finance. This Global Edition has been edited to include enhancements making it more relevant to students outside the United States Using the unifying valuation framework based on the Law of One Price, top researchers Jonathan Berk and Peter DeMarzo set the new standard for corporate finance textbooks. Corporate Finance blends coverage of time-tested principles and the latest advancements with the practical perspective of the financial manager. With this ideal melding of the core with modern topics, innovation with proven pedagogy, Berk and DeMarzo establish the new canon in finance. For programs and professors who would like a streamlined book that is specifically tailored to the topics covered in the first one-semester course, Corporate Finance: The Core is also available by Jonathan Berk and Peter DeMarzo.
Keywords: Empresas -- Finanzas